#TITLE_ALTERNATIVE# - HAMONANGAN SIMATUPANG (NIM: 26912303), HENRI
From previous studies it is known that most of the damage to the pavement caused by heavy vehicles to increase the volume of heavy vehicles has greatly contributed to the damage pavement. Permanent deformation is damage caused by a decrease in the surface of the pavement. This damage occurred because the load received by the road are not able to be borne by the layer or layers of subgrade and pavement on it. While the cracked pavement fatigue is a type of damage that occurs due to repeated load. This damage occurs as a result of the tensile load that occurs in the surface layer exceeds the tensile capacity of pavement materials. The application of a mixture of heavy duty pavement often associated with slow traffic lanes or traffic load is very high static load. This is the concept of pavement that bear the "heavy duty" of heavy vehicles with a number of very heavy loads. Heavy duty pavement is used for the purpose of maintaining the structural condition of roads with heavy vehicle traffic to prevent rapid deterioration. The purpose of this study was to evaluate the performance of hot asphalt mixture Laston AC-WC with Superpave gradation contained in the General Specifications Jasa Marga compared to Laston AC-WC contained in the General Specifications of Highways Agency and the Hot Mix Asphalt (HMA) Superpave kind issued by the Strategic Highway Research Program (SHRP), Asphalt Institute. There are two main components in this study: first is Marshall Stability testing and properties of mixture Laston AC-WC according to specifications Jasa Marga and Laston AC-WC according to the specifications of Highways and the second is a follow-up tests on the performance of fatigue and permanent deformation of the mixture Laston AC-WC Jasa Marga and mixture Laston AC-WC Highways Agency. Testing is done by fatigue testing machine Four Point Loading and Wheel Tracking test machine. Based on the analysis it is concluded that in terms of strength withstand deformation (rutting) due to heavy traffic load indicated by the value of Marshall Stability, Rate of Deformation, Total Deformation and Dynamic Stability, the best performance displayed by mixture Laston AC-WC according to the Highways Agency than mixture Laston AC-WC according to the Jasa Marga.